IMPLEMENTASI TEORI BELAJAR HUMANISTIK PADA MATA PELAJARAN AKIDAH AKHLAK DAN PENGARUHNYA PADA PERILAKU SISWA DI KELAS VIII MTS AL-AS’AD BRAMBANG DIWEK JOMBANG - Nur Ariska; Hidayatur Rohmah (Universitas KH. A. Wahab Hasbullah, 2020)
This study aims to determine the student's behavior on the implementation of humanistic learning theory on the subjects of the Akhlak Creed in Mts Al-As'ad Brambang. To achieve that goal, researchers use data collection techniques through interviews, polls, and documentation. Data is processed using quantitative analysis to determine the implementation of humanistic learning theories on the influence of student behaviour. This research includes the type of field research that is the author doing research directly to the site to obtain and collect data. The results showed that the level of implementation of humanistic learning theory belongs to good category. The level of student behaviour is